Local food system and household responses to external shocks: the case of sustainable coffee farmers and their cooperatives in Western Honduras during COVID-19 - Rodriguez-Camayo, Fernando; Lundy, Mark; Borgemeister, Christian; Ramirez-Villegas, Julian; Beuchelt, Tina (Frontiers in Sustainable Food Systems, 2024)
Introduction The COVID-19 pandemic lockdowns (people confined to home, with movement restrictions) presented an external shock to livelihoods and food systems worldwide, most severely affecting vulnerable households in low-income countries. While evidence is available regarding how COVID-19 generally affected low-income countries, the specific dynamics of local food-system responses and sustainably-certified coffee farm households has not been examined, despite them being usually deemed to be more resilient to shocks. This research examines how local food systems in Honduras changed during lockdowns, how certified coffee households coped with the shock, especially food insecurity, and the potential role of coffee cooperatives in increasing households’ resilience under future shocks and stressors. Methods We applied a mixed-methods approach that combined a structured household survey with semi-structured qualitative interviews with 91 households, 6 cooperative representatives, and 18 food-system representatives. Results We found that coffee-income-dependent households experienced greater food insecurity during lockdown than coffee households with diversified incomes. Before lockdown the local food system was highly dependent on external fresh food from outside the state. Food suppliers changed altered fresh-food procurement strategies, mostly to maintain fresh-food availability at the beginning of the pandemic. However, more than half the interviewed households lacked confidence regarding food security, amid rising food prices and local shortages. Certified coffee cooperatives supported their members by providing food assistance, cash transfers, and credit. Discussion Some of these strategies are difficult to maintain where crises are recurrent and that may render households more vulnerable to future extreme events. Rather, coffee cooperatives could diversify and support their members in growing and marketing additional food crops. This could be a key approach for boosting local food security and strengthening the local food system.